Experimental investigation on the combustion performance of N2 dilution in syngas non-premix combustion in humid air conditions. (25th August 2016) - Tian, Yinshen; Zang, Shusheng; Ge, Bing
Highlights: Syngas non-premix combustion under a wide range of air humidification conditions is investigated. OH-PLIF shows the influences of humidification and N2 dilution on flame. The effects of N2 dilution on emission reduction have great difference under different humidification conditions. Abstract: Diluted combustion is one of the main methods to reduce NOx emissions in syngas combustion. This work studies the performance of syngas non-premix combustion with N2 dilution under different air humidification conditions. OH-PLIF measurement is used to study the flame structure. Temperature and emission of the exhaust is also investigated in the experiment. The results show that in dry air conditions, as the amount of N2 dilution increases, the NOx emission is decreased obviously and CO emission remains lower than 10 ppm. In middle air humidification conditions, NOx emission is lower than all dry air conditions, and CO emission still keeps low. However, the effect of N2 dilution is limited significantly. When in high air humidification conditions, as the amount of N2 dilution increases, CO emission rises significantly, whereas NOx emission changes little. According to the PLIF measurement, the highest flame temperature and the area of reaction zone are reduced to a low level under this condition. The combustion becomes incomplete and results in a significant emission of CO.